1996
DOI: 10.1017/s0263034600010156
|View full text |Cite
|
Sign up to set email alerts
|

Progress with gas lenses

Abstract: Three gas lenses appear promising for fusion and other applications. We review progress of the understanding and scaling of two of these lenses and discuss their potential for industry, advanced research, and fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…where n 0 is the refractive index along its axis, r is the radial distance from the axis and γ is a constant given by the parameters of the SPGL [4]. This implies that only defocus (curvature) is introduced to the wavefront of the passing beam.…”
Section: Spinning Pipe Gas Lensmentioning
confidence: 99%
See 2 more Smart Citations
“…where n 0 is the refractive index along its axis, r is the radial distance from the axis and γ is a constant given by the parameters of the SPGL [4]. This implies that only defocus (curvature) is introduced to the wavefront of the passing beam.…”
Section: Spinning Pipe Gas Lensmentioning
confidence: 99%
“…4. The inverse relationship between focal length and rotation speed for a given pipe wall temperature is typical of such lenses [4]. At high rotation speeds (ω) and large temperatures (T) the lens is strong, typically in the range of a few meters.…”
Section: Spgl Lensingmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated previously, Martynenko 1 demonstrated the theoretical basis of the device which was later demonstrated as a possible practical tool for focusing high-power laser beams. [2][3][4] Using the device as a telescope objective 6 showed that the SPGL is an imperfect lens because the images produced were of low resolution, which we assume was a result of the large number of aberrations generated by the SPGL. This finding inspired us to characterise these aberrations using a CFD model 7,8,10 and direct measurement 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the resulting density distribution inside the pipe is conducive to focusing laser beams through the gradient index (GRIN) lens principle. [1][2][3][4][5][6][7][8] The spinning pipe gas lens was invented by Martynenko 1 , and was subsequently developed for use as a 'damage-free' lens for focusing of high-power laser fields, [2][3][4] and as a gas telescope for astronomical imaging 6 . The principle of operation is simple: the shear viscosity of air increases when heated, 9 such that when the outside wall of the pipe is heated, the layer of air next to the pipe's inner wall is heated as well.…”
Section: Introductionmentioning
confidence: 99%